Karakter Pembelajar Yesus dan Implementasi bagi Guru Pendidikan Agama Kristen di Indonesia - Leiria Meisyani; Nesen Nesen; Maria Lidya Wenas (Anoteros: Jurnal Teologi, 2025)
Christian education in Indonesia encounters difficulties in character development, necessitating an analysis of the attributes of Jesus as a learner to serve as a paradigm for educators. This study seeks to delineate the essential characteristics of Jesus as a learner—openness, empathy, consistency, creativity, and exemplarity—and to recommend their application for Christian Religious Education instructors in Indonesia. The research method used is a theological literature review by analyzing biblical texts and relevant journal articles sourced from databases. Jesus demonstrated openness through dialogue, empathy in service, consistency in integrity, creativity through parables, and exemplary behavior. Practical implementations include interactive classrooms and empathetic teaching. Adopting these attributes enhances the effectiveness of Christian religious education teaching and student character development. Providing actionable guidelines for Christian religious education teachers, it advances contextual theological education in Indonesia.   Pendidikan Kristen di Indonesia menghadapi tantangan dalam pembentukan karakter, mendorong pemeriksaan karakteristik pelajar Yesus sebagai model bagi guru. Studi ini bertujuan untuk mengidentifikasi sifat-sifat utama Yesus sebagai pembelajar—keterbukaan, empati, konsistensi, kreativitas, dan keteladanan—dan mengusulkan implementasinya untuk guru Pendidikan Agama Kristeni di Indonesia. Metode penelitian yang digunakan adalah tinjauan literatur teologis dengan menganalisis teks Alkitab dan artikel jurnal yang relevan yang bersumber dari basis data. Yesus menunjukkan keterbukaan melalui dialog, empati dalam pelayanan, konsistensi dalam integritas, kreativitas melalui perumpamaan, dan teladan dalam tindakan; implementasi praktis termasuk ruang kelas interaktif dan pengajaran empati. Mengadopsi sifat-sifat ini meningkatkan efektivitas pengajaran Pendidikan Agama Kristen dan pengembangan karakter siswa. Memberikan pedoman yang dapat ditindaklanjuti untuk guru Pendidikan Agama Kristen, memajukan pendidikan teologi kontekstual di Indonesia.